An Integrative Model of Customer Relationship Management and Sustainable Finance in SMEs - Noer Rafikah Zulyanti; Elliv Hidayatul Lailiyah; Melita Maharani Putri; Muhammad Khofid Nazarudin; Aqmal Ade Rosyid (Universitas Prasetiya Mulya, 2026)
This study aims to develop an integrative model of Customer Relationship Management (CRM) and Sustainable Finance (SF) in culinary SMEs in Lamongan. The research background is based on the still simple CRM practices and low sustainable finance literacy among business actors. The study used a qualitative-driven mixed methods approach through interviews, observations, and questionnaires with ten culinary SMEs. The results show that although CRM adoption is still limited to manual customer recording and simple loyalty programs, there is great potential to connect it with SF through digitalization, sustainability-based loyalty programs, and the utilization of customer data. The resulting CRM–SF model positions CRM as an enabler to increase customer loyalty while encouraging cost efficiency, green financial literacy, and access to sustainable financing. This research contributes to expanding the function of CRM from a mere marketing tool to a strategic instrument for sustainable financial transformation, while providing practical implications for SMEs, financial institutions, and local governments.